PERLINDUNGAN HUKUM TERHADAP NELAYAN TRADISIONAL INDONESIA MENURUT KETENTUAN UNITED NATIONS CONVENTION ON THE LAW OF THE SEA 1982 - Ida Ayu Febrina Anggasari; I Made Pasek Diantha; Made Mahartayasa (Kertha Negara : Journal Ilmu Hukum, 2015)
Indonesia is a largest archipelagic state in the world that puts Indonesia as a Statewith huge fishermen population. Fishermen is an important community at Indonesia,because without fisherman an archipelagic state will lost its traditional fishing right asmandated by UNCLOS (United Nations Convention on the Law of the Sea 1982) Thiswriting is a normative legal research that uses statutory and fact approaches. It analyzesthe protection on Indonesia’s traditional fisherman based on national regulation andUNCLOS. It also analyzes legal measure that should be done by Indonesia to providelegal protection on their traditional fishermen.